Surgery in Traumatic Injury and Perioperative Considerations - Curry, Nicola; Brohi, Karim (Seminars in Thrombosis and Hemostasis, 2020)
A severely injured patient presents several unique challenges to an admitting trauma team. Not only must the extent of the patient's injuries, particularly those that are life-threatening, be determined within minutes of hospital arrival, but also the trauma team needs to be able to assess whether the patient is bleeding and/or has an attendant coagulopathy. Early management of trauma patients is dictated by the presence (or absence) of significant bleeding. Standard definitive surgical procedures can be conducted in hemodynamically stable patients, but those in hemorrhagic shock should be treated according to damage control resuscitation (DCR) principles. DCR is a practice that has evolved over the last two to three decades, combining limited surgical techniques, which provide early hemorrhage control, and balanced transfusion resuscitation strategies, which mitigate (and ideally) treat trauma-induced coagulopathy (TIC). This review describes the contemporary perioperative management of trauma patients who have significant bleeding and/or TIC and sets out the evidence around the current approach for hemostatic resuscitation in these patients.
Keywords: damage control; hemostatic resuscitation; trauma-induced coagulopathy; perioperative management